The theory of integrated empowerment in the transition to adulthood: concepts and measures - Mouchrek, Najla; Benson, Mark (Frontiers in Sociology, 2023)
Developmental challenges in the transition to adulthood call for a process of empowerment that supports young people in guiding themselves and building capacities toward adult commitments and roles. This work presents an in-depth investigation of empowerment in this life stage and proposes a theory of integrated empowerment aiming to inform interventions to promote positive developmental outcomes for early adults as they navigate experimentation, life choices, and identity construction. This article presents a process of theory construction on empowerment in the transition to adulthood, which includes: an in-depth literature review, a proposition of a theoretical model and a psychometric scale. An empirical study with initial evaluation of the reliability of the measurement scales is also reported. The 18-item scale includes four subscales, each with internal consistency in the high range (.79 to .96) presented in Appendix B). This work is the first stage of a larger interdisciplinary study, aiming to develop interventions to support and improve early adults’ developmental outcomes, particularly oriented toward self-direction, capacity-building, and meaningful integration in society. Because empowerment is recognized as a context- and population- specific construct, we identified the need to build a model addressing specific contexts and challenges of early adulthood. In our model, empowerment is conceptualized as a systemic process that emerges through the ongoing interaction between individual and relational environments. This multidimensional construct is formed by its dimensions and catalysts (personal agency, sense of purpose, mentoring experience, and engagement in community). Each of the catalysts is formed by measurable indicators. The Integrated Empowerment Theory developed in this paper advances and extends previous theoretical propositions, drawing from interdisciplinary theories and emphasizing the nature of empowerment as an interactive, gradual, and multifaceted interplay among developmental experiences at the internal and the external contexts. Finally, a framework for application is proposed, following a logical sequence of implementation of the four catalysts: Community, Agency, Mentors, and Purpose, or CAMP. Despite its possible application to a broad range of early adults, the study focuses primarily on college students, given the universities’ great potential to constitute, by design, empowering settings for youth growth and development in emerging adulthood.